Addition of biochar as thin preamble layer into sand filtration columns could improve the microplastics removal from water - Lichun Hsieh; He, Lei; Mengya Zhang; Wanze Lv; Kun Yang; Meiping Tong (Water Research, 2022)
The release of microplastics (MPs) especially those with sizes less than 10 μm from effluent of wastewater treatment plants (WWTPs) is one of the major sources of plastics into aquatic environment. To reduce the discharge of MPs into environment, it is essential to further enhance their removal efficiencies in WWTPs. In present study, to boost the removal performance of MPs in sand filtration systems (units that commonly employed in WWTPs to remove colloidal pollutants), six types of biochar fabricated from three raw biomass materials (i.e. lignin, cellulose, and woodchips) at two pyrolysis temperatures (400 °C and 700 °C) was respectively amended into sand columns as thin permeable layer. We found that adding all six types of biochar into sand columns as thin permeable layer could greatly improve the retention of MPs with the diameter of 1 μm under either slow (4 m/d) or fast flow rates (160 m/d) due to the high adsorption capability of biochar. Woodchip-derived biochar exhibited the highest MPs retention performance, which was followed by cellulose-derived biochar and then lignin-derived biochar. Moreover, for biochar derived from three raw biomasses, increasing pyrolysis temperature could improve MPs retention performance. The direct observation of real-time plastics retention processes on different types of biochar via a visible flow chamber showed that woodchip-derived biochar especially that fabricated at 700 °C exhibited more MPs trapping processes relative to lignin and cellulose-derived biochar due to their more complex surface morphology. Thus, the highest MPs retention performance was achieved in sand columns with amendment by 1 wt% woodchip-derived biochar fabricated at 700 °C. More importantly, we found that for these modified sand filtration column systems, complete MPs removal could be achieved in real river water and actual sewage water, in multiple filtration cycles, longtime filtration process (100 pore volumes injection) as well as with interval flow conditions. Moreover, biochar could be regenerated and reused as thin permeable layer to effectively remove MPs. The results of this study clearly showed that biochar especially woodchip-derived biochar fabricated at 700 °C had the potential to immobilize MPs especially those with small sizes in WWTPs.
Keywords: Adsorption capacity; biochar; Microplastics; Real-time observation; Sand filtration; Wastewater treatment